Penerapan Model Problem Based Learning (PBL) Berbantuan Media Padlet terhadap Asesmen Sumatif siswa Biologi Fase F - Ifla Safitri; Annika Meizeli; Zikra Zikra (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
This research is motivated by the learning process using group discussion methods, lectures and scientific approaches. The ongoing discussion activities have not run well because they are not heterogeneous so that student involvement in group discussions is not optimal. This results in low student learning outcomes. By implementing a direct learning model that is not optimal, it makes student motivation and understanding of the material low. This study aims to determine the application of the Problem Based Learning (PBL) model assisted by Padlet media on Biology learning outcomes in phase F students at MAN1 West Pasaman (Even Semester 2024/2025). The research method is experimental research. Using two sample classes, namely the experimental class and the control class. The learning process in the experimental class uses the Problem Based Learning (PBL) model assisted by Padlet media while the control class uses a scientific approach. The design used is Randomized Control Group Posttest Only. The sample consists of two classes (experimental and control classes), selected by purposive sampling. The research instrument is in the form of multiple-choice questions through summative assessment. Data were analyzed using the t test. The summative assessment was higher (75.82 > 58.72), there was a significant (t??? > t table). It can be concluded that the Problem Based Learning (PBL) learning model assisted by Padlet media can improve learning outcomes in the summative assessment of students in phase F of MAN 1 West Pasaman. The implications of this research are: 1) Biology teachers can use the Problem Based Learning model assisted by Padlet media to improve students' biology learning outcomes, 2) Other researchers can apply the Problem Based Learning model assisted by Padlet media to different materials and different variables.